A Prospective Study Comparing Polyurethane Film Dressing With Petroleum Gauze Dressing on Split Thickness Skin Graft Donor Sites in Suburban Hospital in Nigeria (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: donor sites; split-thickness skin graft; polyurethane film; petroleum gauze